Política exterior chilena y MERCOSUR : hacia una seguridad subregional con medidas de confianza mutua (2000-2010) - Vera Castillo, Jorge (Estudios Internacionales, 1999)
For a country like Chile, there is a evident need to establish new ties with MERCOSUR –as the main project and institutional framework for subregional integration in South America– that considers not only commercial and economic aspects, but also a political cooperation that incorporates matters of security and defense. In the present work, both elements are analyzed as projection and inherent manifestation of the future Chilean foreign policy. We maintain that the search for a viable subregional security must necessarily go through the realization of solid measures of Mutual Trust, which will make it possible to maintain national integrity within the framework of an open regionalism.